2015
DOI: 10.1007/s11010-015-2635-4
|View full text |Cite
|
Sign up to set email alerts
|

CDK6 mediates the effect of attenuation of miR-1 on provoking cardiomyocyte hypertrophy

Abstract: MicroRNA-1 (miR-1) is approved involved in cardiac hypertrophy, but the underlying molecular mechanisms of miR-1 in cardiac hypertrophy are not well elucidated. The present study aimed to investigate the potential role of miR-1 in modulating CDKs-Rb pathway during cardiomyocyte hypertrophy. A rat model of hypertrophy was established with abdominal aortic constriction, and a cell model of hypertrophy was also achieved based on PE-promoted neonatal rat ventricular cardiomyocytes (NRVCs). We demonstrated that miR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
26
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 25 publications
1
26
0
Order By: Relevance
“…In the present study, miR-1, -133b and -16 were decreased, but miR-21 was increased in the fibrotic myocardium of a mouse Ang-II infusion model, which were consistent with previous reports [2025]. Contrast to the previous reports that miR-214 was upregulated in the myocardium of a rat AAC model, and of a mouse ischemia/reperfusion (IR) injury model and of a rat isoproterenol injection model [1619], our present data showed that miR-214-3p was significantly down-regulated in the myocardium of a mouse Ang-II infusion model, and was upregulated in Ang-II-induced mouse myofibroblasts.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…In the present study, miR-1, -133b and -16 were decreased, but miR-21 was increased in the fibrotic myocardium of a mouse Ang-II infusion model, which were consistent with previous reports [2025]. Contrast to the previous reports that miR-214 was upregulated in the myocardium of a rat AAC model, and of a mouse ischemia/reperfusion (IR) injury model and of a rat isoproterenol injection model [1619], our present data showed that miR-214-3p was significantly down-regulated in the myocardium of a mouse Ang-II infusion model, and was upregulated in Ang-II-induced mouse myofibroblasts.…”
Section: Discussionsupporting
confidence: 94%
“…According to our previous report [20], the recombinant luciferase reporter plasmid containing the potential miR-214-3p binding site sequences of EZH1 and -2 genes were constructed. Using a site-directed mutagenesis kit (TransGen, Beijing, China), the miR-214-3p binding site sequence CCUGCUG was replaced with CCACGAG, CCAGCUG was replaced with CCACGAG to construct the corresponding recombinant luciferase reporter plasmids containing the mutant potential miR-214 binding sequences.…”
Section: Methodsmentioning
confidence: 99%
“…As in our previous report27, the recombinant luciferase reporter plasmids containing the potential miR-26b-5p binding site sequences of the Col1a2 and CTGF genes were constructed. Human embryonic kidney (HEK) 293 cells (3 × 105 cells per well in 12-well plate) were co-transfected with 200 ng of recombinant luciferase reporter plasmid, 20 ng of pRL-TK as an internal control (Promega, Madison, WI), 200 ng of pDsRed2-N1 or 200 ng of pDsRed2-circRNA_000203, 50 nM miR-26b mimic or 50 nM mutant miR-26b mimic (the seed sequence of miR-26b UCAAGUA was changed with UGUUCUA), respectively.…”
Section: Methodsmentioning
confidence: 99%
“…In fact, miR‐1 has been consistently demonstrated to participate in diverse cardiovascular diseases, such as cardiac hypertrophy, arrhythmias and heart failure . Moreover, our previous study has shown up‐regulation of miR‐1 contributes to cardiac electrical remodelling induced by arsenic and atrioventricular block .…”
Section: Discussionmentioning
confidence: 58%
“…[10] Besides, tanshinone IIA relieved ischaemia-induced injury in postinfarction rat by inhibiting miR-1 expression through p38 MAPK signalling pathway. [28] In fact, miR-1 has been consistently demonstrated to participate in diverse cardiovascular diseases, such as cardiac hypertrophy, [29] arrhythmias [30] and heart failure. [31] Moreover, our previous study has shown up-regulation of miR-1 contributes to cardiac electrical remodelling induced by arsenic [32] and atrioventricular block.…”
Section: Discussionmentioning
confidence: 99%